Alone [compact disc, unabridged] : orphaned on the ocean - Logan, Richard D., 1942- (Tantor Audio, 2010)
Co-authored by a renowned psychologist and survival expert, this book delves into the details of how a little girl survived the at-sea murder of her family; the pod of whales who guarded her; and the aftermath and the recapturing of life.